Um estudo sobre a geometria apresentada nos projetos pedagógicos curriculares das universidades estaduais paranaenses à luz das atuais regulamentações - Freitas, Gabriela Daiani (2022)
Geometry is an important branch of Mathematics, it is present in the curriculum of Basic Education, and there are many in favor of its effective teaching at all educational levels, as it can develop, among other aspects, reasoning and visual perception, favoring the processes of abstraction and generalization. In addition, it is formative and provides tools for human beings to understand and interpret their world, as well as favoring the processes of abstraction and generalization. Such content must undergo changes in its curricular proposals, with the changes promoted in the norms that guide the education systems, combined with the Common National Curriculum Base (BNCC) (BRASIL, 2018), which also managed to affect teacher training courses, with Resolution CNE/CP nº 2, which establishes the Common National Base for the Initial Training of Basic Education Teachers – BNCC Training (BRAZIL, 2019). Thus, in this investigation the objective is to analyze the Pedagogical Projects of the Courses - PPC - of Licentiate in Mathematics, of the seven public universities of Paraná, to identify how the contents of Geometry are organized in the formation of the licentiate in the light of the objectives proposed by the current regulations. The research has an exploratory character and uses a bibliographic survey, in which we seek, through the different regulations that govern the levels of elementary, secondary, and higher education, to understand and present how the learning objectives related to the contents of Geometry to then assess whether the demands requested by these documents are being met by the initial training courses, based on their PPC. For the data analysis methodology, a qualitative approach is used, supported by Content Analysis. As a result, it is pointed out that, when pairing the objects of knowledge and related skills in the BNCC and in the Paraná Curricular Reference – RCP (PARANÁ, 2018;2021), it was found that the topics covered in the disciplines are in line with the Geometry content present in the curriculum.